Preparation of Orientation and Mobility Specialist Students Who are Blind and Have Low Vision: Survey of Faculty Who Teach Blindfold and Simulation Cane Courses. (July 2019) - Griffin-Shirley, Nora; Bozeman, Laura; Obiero, Nereah A.; Steinle, Kyle J.; Page, Anita
Introduction: The purpose of this study was to survey the faculty of personnel preparation programs that train orientation and mobility (O&M) specialists in the identification of accommodations, teaching techniques, and resources needed to teach students who are visually impaired (i.e., those who are blind or have low vision) and who are enrolled in blindfold and simulation cane courses (hereafter, cane courses). Cane courses are used to teach the techniques of independent cane travel, and they require total visual occlusion using blindfolds as well as simulated low vision using goggles that depict different visual acuities and field losses. Methods: This study surveyed personnel preparation programs training O&M specialists with an online questionnaire with open-ended items to identify the program's required accommodations, teaching techniques, and resources needed to teach visually impaired students who are enrolled in cane courses. The survey was e-mailed to 22 universities in North America, which have personnel preparation programs for O&M specialists and asked for responses from individuals who teach cane courses. Descriptive statistics were used to analyze the survey data. Results: Results showed that the format of the cane courses was varied, a variety of accommodations and teaching strategies were used, and the universities' office of disabled students generally did not know how to accommodate these courses. Discussion: A need exists for a student who is visually impaired to be an experienced traveler and to be knowledgeable about what accommodations and strategies he or she will use when they need to teach a fellow student during a cane course. Visually impaired students must be able to monitor the safety of their peers as well as the changing dynamics of the environment in which they are working. Implication for practitioners: To effectively teach visually impaired students who are enrolled in cane courses, university faculty teaching these courses could request prospective visually impaired students to provide documentation regarding their travel skills prior to acceptance into a personnel preparation program in O&M. In addition, students with visual impairments need to discuss with their universities' office of disabled students and legal counsel what reasonable accommodations are relevant for visually impaired students enrolled in the cane courses and what accommodations they believe the universities are committed to providing these students.